Corporate governance failures : the role of institutional investors in the global financial crisis - Hawley, James P. (EBL-Schweitzer, 2011)
Legal and financial practitioners and researchers investigate the role of institutional investors in the corporate governance failures that contributed to the recent global financial crisis. The authors also offer proposals to mitigate future pitfalls. This volume covers alternative financial investments, systemic risk, and responsible investment.- Resumé vydavatel